HUBUNGAN PERSEPSI PERAWAT TENTANG PERILAKU AGRESIF PASIEN DENGAN SIKAP PERAWAT DALAM MERAWAT PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PEMERINTAH ACEH - Denafianti Denafianti; Satria Safirza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Nurses are the people who are most often involved in handling the aggressive behavior of patients, so nurses are at risk of receiving acts of violence from clients. Aggressive behavior shown by patients greatly disrupts the comfort of the care room including other patients and nurses. Nurses tend to be victims in the event of a client's aggressive behavior. Nurses must face violence both verbally and physically that happens almost every day. To anticipate this, professional skills in managing clientsâ€ aggressive behavior are needed. The purpose of this study was to determine the relationship between nursesâ€ perceptions of the aggressive behavior of patients with nursesâ€ attitudes in caring for schizophrenic patients in the Aceh Mental Hospital in 2019. The study design was a descriptive correlation through a cross-sectional approach. The study was carried out on December 17 to 2018. The population of this research is 47 nurses on duty. The results of the study showed that there was a correlation between perceptions originating within the nurse (Self-Perception) (p = 0,000), perceptions outside the nurse (External Perception) (p = 0,007), correlation perception of nurses (p = 0,000) about aggressive behavior patient and a nursesâ€™ attitude in caring for schizophrenic patients at the Aceh Government Mental Hospital. It can be concluded that there is a correlation between nursesâ€ perceptions of the aggressive behavior of patients with nursesâ€ attitudes in treating schizophrenic patients. It is expected that this research can be a recommendation for nurses who have perceptions and attitudes that are not optimal in caring schizophrenic patients with aggressive behavior so that it will be positive motivation in treating schizophrenic patients and be able to overcome aggressive behavior.Keywords: Perception, Attitude, Aggressive Behavior, Nurse